Quality of life among adult patients living with diabetes in Rwanda: a cross-sectional study in outpatient clinics - Per Kallestrup; Charilaos Lygidakis; Claus Vögele; Jean Paul Uwizihiwe; Michela Bia; Francois Uwinkindi (BMJ Open)
Objectives To report on the disease-related quality of life of patients living with diabetes mellitus in Rwanda and identify its predictors.Design Cross-sectional study, part of the baseline assessment of a cluster-randomised controlled trial.Setting Outpatient clinics for non-communicable diseases of nine hospitals across Rwanda.Participants Between January and August 2019, 206 patients were recruited as part of the clinical trial. Eligible participants were those aged 21–80 years and with a diagnosis of diabetes mellitus for at least 6 months. Illiterate patients, those with severe hearing or visual impairments, those with severe mental health conditions, terminally ill, and those pregnant or in the postpartum period were excludedPrimary and secondary outcome measures Disease-specific quality of life was measured with the Kinyarwanda version of the Diabetes-39 (D-39) questionnaire. A glycated haemoglobin (HbA1c) test was performed on all patients. Sociodemographic and clinical data were collected, including medical history, disease-related complications and comorbidities.Results The worst affected dimensions of the D-39 were ‘anxiety and worry’ (mean=51.63, SD=25.51), ‘sexual functioning’ (mean=44.58, SD=37.02), and ‘energy and mobility’ (mean=42.71, SD=20.69). Duration of the disease and HbA1c values were not correlated with any of the D-39 dimensions. A moderating effect was identified between use of insulin and achieving a target HbA1c of 7% in the ‘diabetes control’ scale. The most frequent comorbidity was hypertension (49.0% of participants), which had a greater negative effect on the ‘diabetes control’ and ‘social burden’ scales in women. Higher education was a predictor of less impact on the ‘social burden’ and ‘energy and mobility’ scales.Conclusions Several variables were identified as predictors for the five dimensions of quality of life that were studied, providing opportunities for tailored preventive programmes. Further prospective studies are needed to determine causal relationships.Trial registration number NCT03376607.